Amelogenesis Imperfecta and Screening of Mutation in Amelogenin Gene. (19th June 2014) - Oliveira, Fernanda Veronese; Gurgel, Carla Vecchione; Kobayashi, Tatiana Yuriko; Dionísio, Thiago José; Neves, Lucimara Teixeira; Santos, Carlos Ferreira; Machado, Maria Aparecida Andrade Moreira; Oliveira, Thais Marchini
Abstract : The aim of this study was to report the clinical findings and the screening of mutations of amelogenin gene of a 7-year-old boy with amelogenesis imperfecta (AI). The genomic DNA was extracted from saliva of patient and his family, followed by PCR and direct DNA sequencing. The c.261C>T mutation was found in samples of mother, father, and brother, but the mutation was not found in the sequence of the patient. This mutation is a silent mutation and a single-nucleotide polymorphism (rs2106416). Thus, it is suggested that the mutation found was not related to the clinical presence of AI. Further research is necessary to examine larger number of patients and genes related to AI.